PENGARUH MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) BERBANTUAN PERMAINAN CURIK-CURIK UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V GUGUS III KECAMATAN TEJAKULA (Adi Widya: Jurnal Pendidikan Dasar, 2023)
This study aims to determine the effect of the STAD (Student Teams Achievement Division) model assisted by the Curik-Curik Game to increase motivation to learn Mathematics in class V at SD Gugus III Tejakula District. The research was conducted using Quasi-Experimental or Quasi-Experimental research by applying the Post-Test Only Control Group Design. This study used a population of all fifthgrade students at SD Gugus III Tejakula District with a total of 209 students. The selection of the sample was carried out by using a random sampling lottery method. As many as 30 students from grade V SD Negeri 6 Tejakula were assigned to be the experimental group and 24 students from grade V SD Negeri 3 Tejakula were assigned to be the control group. Data collection was carried out through a questionnaire instrument and documentation which was processed using SPSS Version 25. Data processing included validity tests, reliability tests, normality tests, homogeneity tests, and t tests. Based on the results of data analysis, it is known that there is a significant difference in the STAD (Student Teams Achievement Division) Model assisted by Curik-Curik Games to increase motivation to learn Mathematics in class V at SD Gugus III Tejakula District. The thit value is 5,799 > ttable 1,674. It is known that the average1 learning motivation of students in the experimental class was 123.10, and the average learning motivation in the control class was 110.45. Thus the average value of learning motivation in the experimental class is greater than the control class. Therefore, the intervention method applied has an effect on students' learning motivation.